Production costs of agroecological products, in small family producers scale of the Agroecological Fair UNIMINUTO, Colombia - Chaparro Africano, Adriana María; Salazar Soto, Nayeth (Cooperativismo & Desarrollo, 2020)
This applied research was carried out between 2017 and 2018 with producers from the Agroecological Fair UNIMINUTO - FAU in Bogotá. Its objective was to analyze the production costs of agro-ecological goods obtained by small-scale family producers, because sales in this space have not significantly increased throughout its history (2012 to 2018), and due to the permanent claim of buyers because of the high sale prices. To achieve the objective, a calculation of costs methodology was selected (Chaparro, 2017), which was adapted and applied to 33 products - fresh, processed, cleaning and ornamental plants — from 15 producers. After collecting the information in a costs form, an analysis was performed of production costs by product, which was then compared with the available literature —21 documented production systems. As a result, of the 15 producers, 80% do not keep production records, 26% do not know their costs, and 37% have no sales records.